Analytical model for prediction of strength and fracture paths characteristic to randomly oriented strand (ROS) composites. (1st July 2016) - Selezneva, Marina; Roy, Steven; Lessard, Larry; Yousefpour, Ali
Abstract: There is an emerging interest in the aerospace industry to manufacture composite components with intricate geometries. One way to do this is by using a bulk moulding compound which consists of strands of unidirectional carbon-fibre tape. This material system is termed randomly-oriented strand (ROS) composites. The great design potential of ROS composites has been demonstrated in the literature, but the modelling techniques for this material are in their infancy. This paper proposes a stochastic 2D modelling technique for predicting strength of ROS composites from the mechanical properties of the individual strands. This model is representative of the microstructure and the through-the-thickness fracture morphologies characteristic to ROS composites. Classical laminate theory and Hashin's criteria are used to predict strand breakage, while interlaminar strength and fracture toughness are implemented to account for strand debonding. The model successfully predicts the strength of ROS composites, captures the effect of strand size on properties, depicts heterogeneous nature of the material, and demonstrates that failure follows the "weakest-link" principle. It also indicates that thermoplastic ROS composites are superior to their thermoset (e.g. epoxy) counterparts.